SSC Graduate Students’ Difficulties in Doing Research - Ocbian, Magdalena M.; Gamba, Michael P. (JPAIR Institutional Research, 2015)
Research has become an integral part of learning. Thus, students’ capabilities of doing research need to be strengthened. The study aimed to determine the difficulties of students at Sorsogon State College, Philippines-School of Graduate Students which may serve as a basis for an intervention program. Respondents in this study are the 93 students who have taken Research Methodology subject at SSC School of Graduate Studies. It utilized the descriptive-developmental research design. Data gathering was primarily done through survey questionnaire and supplemented with unstructured interview and focus group discussion. Descriptive statistics was utilized to summarize the data. Results showed that the respondents encountered much difficulty in conceptualizing a research problem/ title, looking for and reviewing related literature and studies, determining the correct research methodology and procedures to be used, determining the appropriate statistical tools, gathering the data, and analyzing and interpreting the data. Among the factors identified which hinder them from doing research are heavy teaching loads, lack of motivation and commitment, and financial constraints. There are interventions that are proposed to enhance the students’ capabilities in conducting quality researches.